(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Stroke is a significant global health and social problem. Patients with comorbidities like diabetes, hypertension, or cardiac diseases have a greater risk of developing stroke. To prevent stroke and improve stroke patients’ prognosis, awareness should be raised primarily in high-risk individuals. Objectives: To assess knowledge and awareness of stroke risk factors and warning signs among heart disease patients in Saudi Arabia. Methods: This is a survey questionnaire-based cross-sectional study targeting Saudi cardiac patients who are over 18 years of age. The questionnaire consisted of 38 questions aimed to assess the awareness of stroke in cardiac patients. The collected data was forwarded to the SPSS program, version 25, where statistical analysis was carried out. Results: As regard knowledge and awareness score about stroke, (46.8%) of the participants, exhibited a high level of knowledge, suggesting a commendable level of understanding and familiarity with stroke-related assessments. Furthermore, nearly 29%, demonstrated a moderate level of knowledge. The remaining 24.3% of participants reported a low level of knowledge. Moreover, (85.7%) recognized high blood pressure as a significant risk factor to the development of stroke and speech problems (71.1%) as warning signs of stroke. Conclusion: Nearly half of the participants demonstrated a high level of knowledge regarding stroke, with a substantial portion showing moderate understanding. It is promising that the majority recognized high blood pressure, smoking, diabetes, and cardiac disease as significant risk factors for stroke. However, there is room for improvement, especially in understanding warning signs such as sudden memory loss and double vision.